Secondary science teachers’ use of the affective domain in science education - Grauer, Bette L. (Kansas State University, 2014)
The purpose of this qualitative case study was to explore (a) the types of student affective responses that secondary science teachers reported emerged in science classes, (b) how those teachers worked with student affective responses, and (c) what interactions were present in the classroom when they worked with student affective responses. The study was motivated by research indicating that student interest and motivation for learning science is low. Eight secondary science teachers participated in the case study. The participants were selected from a pool of teachers who graduated from the same teacher education program at a large Midwest university. The primary sources of data were individual semi-structured interviews with the participants. Krathwohl’s Taxonomy of the Affective Domain served as the research framework for the study. Student affective behavior reported by participants was classified within the five levels of Krathwohl’s Affective Taxonomy: receiving, responding, valuing, organization, and characterization. Participants in the study reported student behavior representing all levels of the Affective Taxonomy. The types of behavior most frequently reported by participants were identified with the receiving and responding levels of the Affective Taxonomy. Organization behavior emerged during the study of perceived controversial science topics such as evolution. Participants in the study used student affective behavior to provide feedback on their lesson activities and instructional practices. Classroom interactions identified as collaboration and conversation contributed to the development of responding behavior. The researcher identified a process of affective progression in which teachers encouraged and developed student affective behavior changes from receiving to responding levels of the Affective Taxonomy.
Keywords: Science education; Science Education (0714)